Constraining planet formation around 6–8 M⊙ stars. Issue 1 (3rd February 2020) - Veras, Dimitri; Tremblay, Pier-Emmanuel; Hermes, J J; McDonald, Catriona H; Kennedy, Grant M; Meru, Farzana; Gänsicke, Boris T
ABSTRACT: Identifying planets around O-type and B-type stars is inherently difficult; the most massive known planet host has a mass of only about $3\, M_{\odot }$ . However, planetary systems which survive the transformation of their host stars into white dwarfs can be detected via photospheric trace metals, circumstellar dusty and gaseous discs, and transits of planetary debris crossing our line of sight. These signatures offer the potential to explore the efficiency of planet formation for host stars with masses up to the core-collapse boundary at $≈ 8\, M_{\odot }$, a mass regime rarely investigated in planet formation theory. Here, we establish limits on where both major and minor planets must reside around $≈ 6\rm {-}8\, M_{\odot }$ stars in order to survive into the white dwarf phase. For this mass range, we find that intact terrestrial or giant planets need to leave the main sequence beyond approximate minimum star–planet separations of, respectively, about 3 and 6 au. In these systems, rubble pile minor planets of radii 10, 1.0, and 0.1 km would have been shorn apart by giant branch radiative YORP spin-up if they formed and remained within, respectively, tens, hundreds, and thousands of au. These boundary values would help distinguish the nature of the progenitor of metal pollution in white dwarf atmospheres. We find that planet formation around the highest mass white dwarf progenitors may be feasible, and hence encourage both dedicated planet formation investigations for these systems and spectroscopic analyses of the highest mass white dwarfs.